G-CSF-Primed Peripheral Blood Stem Cell Haploidentical Transplantation Could Achieve Satisfactory Clinical Outcomes for Acute Leukemia Patients in the First Complete Remission: A Registered Study - Ma, Yan-Ru; Zhang, Xiaohui; Xu, Lanping; Wang, Yu; Yan, Chenhua; Chen, Huan; Chen, Yuhong; Han, Wei; Wang, Fengrong; Wang, Jingzhi; Liu, Kaiyan; Huang, Xiaojun; et al. (Frontiers in Oncology, 2021)
G-CSF-mobilized peripheral blood (G-PB) harvest is the predominant graft for identical sibling donor and unrelated donor allogeneic hematopoietic stem cell transplantation (HSCT) recipients, but it was controversial in haploidentical related donor (HID) HSCT. In this registry study, we aimed to identify the efficacy of HID G-PB HSCT (HID-PBSCT) for acute leukemia (AL) patients in first complete remission (CR1). Also, we reported the outcomes for the use of G-PB grafts in comparison with the combination of G-BM and G-PB grafts in HID HSCT recipients. Sixty-seven AL patients in CR1 who received HID-PBSCT were recruited at the Institute of Hematology, Peking University. Patients who received haploidentical HSCT using the combination of G-BM and G-PB harvests in the same period were enrolled as controls (n=392). The median time from HSCT to neutrophil and platelet engraftment was 12 days (range, 9-19 days) and 12 days (range, 8-171 days), respectively. The 28-day cumulative incidence of neutrophil and platelet engraftment after HSCT was 98.5% and 95.5%, respectively. The cumulative incidences of grade II-IV and grade III-IV acute graft-versus-host disease (GVHD) were 29.9% (95%CI 18.8%-40.9%) and 7.5% (95%CI 1.1%-13.8%), respectively. The cumulative incidences of total and moderate-severe chronic GVHD were 54.9% (95%CI 40.9%-68.8%) and 17.4% (95%CI 6.7%-28.0%), respectively. The cumulative incidences of relapse and non-relapse mortality were 13.9% (95%CI 5.4%-22.5%) and 3.4% (95%CI 0-8.1%), respectively. The probabilities of overall survival (OS) and leukemia-free survival (LFS) were 84.7% (95%CI 74.7%-94.7%) and 82.7% (95%CI 73.3%-92.1%) respectively. Compared with the HID HSCT recipients using the combination of G-BM and G-PB grafts, the engraftments of neutrophil and platelet were both significantly faster for the G-PB group, and the other clinical outcomes were all comparable between the groups. In multivariate analysis, graft types did not influence the clinical outcomes. Overall, for the patients with AL CR1, G-PB graft could be considered an acceptable graft for HID HSCT recipients. This study was registered at https://clinicaltrials.gov as NCT03756675.